A camerate crinoid from the Upper Silurian (Ludlow) Moydart Formation of Nova Scotia, Canada - Donovan, Stephen; Pickerill, Ron (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1995)
Well-preserved fossil cchinodcrms are uncommon in the Arisaig Group (early Silurian to early Devonian) of Nova Scotia. Although not preserving sufficient detail to enable specific identification, a crinoid, monobathrid camerate gen. et sp. indet. from the Moydart Formation (late Silurian, late Ludlow), shows the following features: a long, hetcromorphic (N212) column of circular section and with convex nodals; a broad, conical dorsal cup with broad, high radials; fixed, uniserial arms which branch twice; 20 long, free arms that are uniserial most proxi-mally, but are otherwise biserial; and numerous, elongate, blade-like pinnules. The column of this species differentiates it from a second taxon commonly preserved perpendicular to bedding in the Moydart Formation. Thus, while one species in this formation is preserved autochthonously in life position, another forms a crinoid lagersUtte and coquinas of more complete specimens, but is, at best, parautochthonous.